2017
DOI: 10.1177/2054358117703059
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Patients With Chronic Kidney Disease in the Primary Care Setting: A Retrospective Cohort Study From Ontario, Canada

Abstract: Background:Patients with chronic kidney disease may not be receiving recommended primary renal care.Objective:To use recently established primary care quality indicators for chronic kidney disease to determine the proportion of patients receiving recommended renal care.Design:Retrospective cohort study using administrative data with linked laboratory information.Setting:The study was conducted in Ontario, Canada, from 2006 to 2012.Patients:Patients over 40 years with chronic kidney disease or abnormal kidney f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 53 publications
1
35
1
1
Order By: Relevance
“…14 In the Netherlands, the ACR testing rate was 40% among patients with stage 3 CKD, although a 15-month time frame was used. 15 In Canada, only half of the patients received follow-up ACR tests after an initial abnormal kidney test, 16 while others have reported that ACR monitoring was performed for only 16% of the patients with a low eGFR. 12 In this study, patients with CKD who also had diabetes were better monitored, compared with patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the Netherlands, the ACR testing rate was 40% among patients with stage 3 CKD, although a 15-month time frame was used. 15 In Canada, only half of the patients received follow-up ACR tests after an initial abnormal kidney test, 16 while others have reported that ACR monitoring was performed for only 16% of the patients with a low eGFR. 12 In this study, patients with CKD who also had diabetes were better monitored, compared with patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The prescribing of an ACEI or ARB in patients with CKD with albuminuria was slightly lower in Australian general practice compared to that reported in other developed nations [24][25][26][27]. Studies from different provinces of Canada [24][25][26] investigating prescribing in CKD patients reported rates of 74% to 80% for ACEI or ARB prescribing, while a study conducted in the Netherlands found prescribing in 78% and 82% of non-diabetes and diabetes patients, respectively [11]. The reason for the low rate of ACEI/ARB prescribing could be non-concordance to Australian CKD treatment guidelines, including not referring patients to nephrology care [3].…”
Section: Discussionmentioning
confidence: 57%
“…Despite strong evidence for the efficacy of ACEI/ARB to reduce proteinuria and slow progression of CKD to ESKD, less than 70% of Australian adult patients with CKD stages 3-5 with diabetes and microalbuminuria were receiving an ACEI or ARB. The prescribing of an ACEI or ARB in patients with CKD with albuminuria was slightly lower in Australian general practice compared to that reported in other developed nations [24][25][26][27]. Studies from different provinces of Canada [24][25][26] investigating prescribing in CKD patients reported rates of 74% to 80% for ACEI or ARB prescribing, while a study conducted in the Netherlands found prescribing in 78% and 82% of non-diabetes and diabetes patients, respectively [11].…”
Section: Discussionmentioning
confidence: 86%
“…The prescribing of an ACEI or ARB in patients with CKD with albuminuria was slightly lower (5-10%) in Australian general practice compared to other developed nations (8,(21)(22)(23). Furthermore, the proportion of patients prescribed at least two RAS blockers concurrently was 7.6%, which is double the proportion (3.7%) reported by the Netherlands study (11) using the same indicator.…”
Section: Discussionmentioning
confidence: 68%
“…The prescribing percentage was even lower (62.3%) in those patients with macroalbuminuria. Studies from different provinces of Canada (8,21,22) in CKD reported rates of 74% to 80% for ACEI or ARB prescribing, while the Netherlands study found prescribing in 78% and 82% of non-diabetes and diabetes patients, respectively (11). Similar to our study, the percentages of prescribing of an ACEI or ARB reported by studies in Canada and the Netherlands (8,11,21,22) were higher in CKD patients with diabetes compared to those without diabetes.…”
Section: Discussionmentioning
confidence: 99%